Clover Hendry's day off - Morrey, Beth (G. P. Putnam's Sons, 2024)
"A hilarious and empowering perimenopausal Ferris Bueller's Day Off, about Clover Hendry, 46, and the day she decides to stop keeping the plates spinning, say F@#! it all, and finally get hers"--